The production of potassium permanganate from local manganese ores - Pigao, Concepcion G.; Sanchez, Angelina M. (1979)
After series of experiment, the optimum conditions under which potassium permanganate may be produces form local manganese ore with 50% KOH and KC103 at a roasting temperature of 300 Celsius , 2 hr roasting time and at a ratio of 1:3:2 for Mn ore:KOH:KC103. The calcine (K2Mn04) obtained is leached with hot water, allowed to stand for several hours, filtered by suction and a currents of C02 passed through the solution. The resulting solution (KMn04) is filtered by suction again, and finally evaporated to crystallization.